The New Face of Political Islam in Central Asia: The Rise of Islamo-democrats. Issue 2 (2nd April 2016) - Karagiannis, Emmanuel
Abstract: Political Islam in Central Asia is currently undergoing a transitional phase. Radical groups such as the Islamic Movement of Uzbekistan and Hizb ut-Tahrir no longer monopolize the Islamist scene. There is now a new generation of Islamist leaders in Kyrgyzstan, Kazakhstan, and Tajikistan that advocate a public role for Islam without seeking regime change. They can be called Islamo-democrats because they participate in elections and recognize the constitutional process. The article will examine and compare the biography, political career, and beliefs of three representatives of this political trend: Tursunbai Bakir Uulu, Bekbolat Tleukhan, and Mohiddin Kabiri. It will claim that the emergence of Islamo-democrats is partly the result of developments in Turkey, especially the rise to power of the Adalet ve Kalkinma Partisi . Two factors account for the Turkish influence in Kyrgyzstan, Kazakhstan, and Tajikistan: the successful diffusion of ideological norms and the importance that governments attach to maintaining good relations with Turkey.